Pola Peresepan Obat Diare Pada Balita di Rawat Jalan Rumah Sakit Khusus Ibu dan Anak Sadewa Periode Januari – Juni 2022 - Hanita Christiandari; Jarot Yogi Hernawan; Aprilia Siti Nur Hidayyah (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2023)
Diarrhea is a condition in which a person has bowel movements with a soft or liquid consistency, it can even be just water and the frequency is more frequent in one day. Diarrheal disease in toddlers is ranked 2 out of the top 10 childhood diseases at the Sadewa Mother and Children Hospital (RSKIA) in May 2022. Knowing the pattern of prescribing diarrhea drugs in toddlers in outpatient care at the Sadewa Mother and Children Hospital for the period January - June 2022. The research conducted was a non-experimental descriptive research with a retrospective method. The study was conducted by taking prescription data from electronic medical records at the Sadewa RSKIA pharmacy and then recording them on a data collection sheet. Data were analyzed using tabulations in the form of percentages (%). The results showed that out of 130 samples, the profile of diarrhea patients under five was dominated by males, 77 children (59%), aged 2-3 years 65 children (50%), and the degree of dehydration of patients without dehydration, 120 children (92%). ). The most widely used drug class was zinc with 120 prescriptions (34.3%), zinc has a protective effect against diarrhea and can reduce recurrence and probiotics with 119 prescriptions (33.8%), probiotic bacteria will help the process of nutrient absorption and prevent disturbances in water absorption. The dominating combination was a combination of 3 drugs namely electrolytes, zinc and probiotics 69 prescriptions (57%), oralit functioned to replace fluids and electrolytes in the body that are wasted during diarrhea, zinc supplementation and probiotics in diarrhea effectively reduced stool output. The rule for using the treatment of diarrhea in toddlers is mostly 1 time a day with a total of 132 drugs (37.7%). The dominating drug was zinc with 117 prescriptions (88.6%) The pattern of prescribing diarrhea drugs in toddlers in this study was dominated by male patients, aged 2-3 years with a degree of dehydration, patients without dehydration. The most widely used drug classes are zinc and probiotic groups. The most common drug combination found is a combination of 3 drugs, namely electrolyte, zinc and probiotic group drugs. The rule for using the treatment of diarrhea in most toddlers is 1 time a day.